Elaboración de un folleto para capacitación a docentes sobre psicomotricidad, en la “Escuela Club Femenino Cotopaxi” de la provincia de Cotopaxi, cantón Latacunga, barrio San Martín, en el periodo” 2012- 2013 - Pulloquinga Montaluisa, Amparo E. (2015)
This research is elaborated with the aim of providing capitation to teachers on the development of motor skills, and be able to transmit significant knowledge that will be beneficial for the development of skills and psychomotor skills, enabling them to function children / as in everyday life, it is noteworthy that this work will serve as a support tool for teachers could use in the teaching-learning process. The first years of a child's life / a, are essential for comprehensive biological and social development, and this is where the infant acquires motor, sensory, affective, cognitive functions either in the family, social environment or the environment in which it operates . The lack of teacher training, carelessness of governments passing, lack of economic resources, produce children do not develop in full abilities and skills in its initial stage, that leads to a series of future problems where always the most affected is the infant....